Frege and other philosophers - Dummett, Michael, 1925-2011.; Oxford eBooks (Oxford : Clarendon, 1991)
This book deals with Frege's philosophy by comparing and contrasting his views with those of other philosophers, mostly contemporary with him.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Frege, Gottlob, -- 1848-1925.; Frege, Gottlob, -- 1848-1925 -- Influence; Logic, Symbolic and mathematical; Analysis (Philosophy); Electronic books